When Promising Interventions Fail: Personalized Coaching for Teachers in a Middle-Income Country - Pedro Carneiro; Yyannú Cruz-Aguayo; Ruthy Intriago; Juan Ponce; Norbert Schady; Sarah Schodt (Institute of Labor Economics (IZA), 2022)
Children in developing countries have deep deficits in math and language. Personalized coaching for teachers has been proposed as a way of raising teacher quality and child achievement. We designed a coaching program that focused on one aspect of teacher quality—teacher-child interactions—that researchers in education and psychology have argued is critical for child development and learning. We implemented the coaching program in Ecuador, with 100 1st grade teachers randomly assigned to treatment and 100 to control. Coaching improved the quality of teacher-child interactions but reduced child achievement. Our results underline the importance of evaluating new forms of professional development for teachers, even those that follow best practice, before these interventions are taken to scale.
Keywords: I20; 330; teacher quality; coaching